Monitoring the Monitor: Distracted Institutional Investors and Board Governance - Liu, Claire; Low, Angie; Masulis, Ronald W; Zhang, Le (Review of Financial Studies, 2020)
Abstract Boards are crucial to shareholder wealth. Yet little is known about how shareholder oversight affects director incentives. Using exogenous shocks to institutional investor portfolios, we find that institutional investor distraction weakens board oversight. Distracted institutions are less likely to discipline ineffective directors with negative votes. Consequently, independent directors face weaker monitoring incentives and exhibit poor board performance; ineffective independent directors are also more frequently appointed. Moreover, we find that the adverse effects of investor distraction on various corporate governance outcomes are stronger among firms with problematic directors. Our findings suggest that institutional investor monitoring creates important director incentives to monitor.